Evidence and implications of direct charge excitation as the dominant mechanism in plasmon-mediated photocatalysis - Calvin Boerigter (Nature Portfolio, 2016)
The excitation of metal nanoparticles with light can lead to localized surface plasmon resonances, capable of driving chemical reactions in bound species. Here, the authors elucidate this mechanism and suggest that future plasmonic catalysts may be able to selectively activate specific chemical bonds.